Optimizing electro-luminescence processes in organic light-emitting diodes - Divayana, Yoga (2008)
Organic electronic and photonic devices have attracted great attention in recent years due to their unique properties. From electronic point of view, organic materials show capability similar to their inorganic counterpart of transporting charges, producing light and even magnetism. Mechanically, organic is a soft material which can be processed at low temperature. This thesis focuses on the photonic side of the technology – the organic light-emitting diode (OLED). OLED makes use of organic material to produce light by injecting both holes and electrons from two different terminals, respectively. Before emission of light, the electron and hole recombine to form a quasi-particle called the excitons. During this process, not all the carriers contribute to the recombination. The reason for this is the imbalance of carrier injection and transportation within the device. Firstly, we investigate the controversial role of copper-phthalocyanines which is commonly used to balance the carriers. We also introduce two different methods to solve the electron-hole imbalance problem: (1) by adding a thin layer of hole blocking layer to truly block hole-carrier within the device, (2) by using an electron transporting layer to also block the hole-carrier to balance the carrier. Recombination of electron and hole is occurred in the area called the emission layer.